Wpływ gatunków domieszkowych i współpanujących na wysokość i pierśnicę jodły (Abies alba Mill.) oraz zasobność drzewostanów jodłowych w Karpackiej Krainie Przyrodniczo-Leśnej - Pach, Maciej (Leśne Prace Badawcze, 2010)
The best growth function for silver fir was selected from 30 models, based on adequacy of height and DBH approximation, as well as growing stock, in the pure fir stands on the fertile mountain and highland sites. This model was then applied to evaluate the growth of fir in mixed (rather than pure) stands growing together with different proportions of spruce, beech and sycamore. It was found that the DBH of fir at a given age is larger in some stands with admixture of beech and spruce than in pure fir stands, although no such relationship was found for height. At the fertile mountain (LG) site and highland forest (Lwyż) site, fir stands reached the highest growing stock. At the mixed mountain (LMG) forest site the growing stock of fir stands with admixtures of different species, especially a relatively high proportion of spruce, was greater than in pure fir stands. At the LG site the lowest growing stock was in fir stands with admixture of beech and spruce, in which the proportion of beech was higher than that of spruce. Fir stands with admixture of spruce and sycamore alone had a lower growing stock than pure fir stands.